2010
DOI: 10.1021/jp108695z
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Geometries, Stabilities, and Electronic Properties of the Bimetallic M2-doped Aun (M = Ag, Cu; n = 1−10) Clusters: Comparison with Pure Gold Clusters

Abstract: The density functional method with relativistic effective core potential has been employed to investigate systematically the geometrical structures, relative stabilities, growth-pattern behaviors, and electronic properties of small bimetallic M(2)Au(n) (M = Ag, Cu; n = 1-10) and pure gold Au(n) (n ≤ 12) clusters. The optimized geometries reveal that M(2) substituted Au(n+2) clusters and one Au atom capped M(2)Au(n-1) structures are dominant growth patterns of the stable alloyed M(2)Au(n) clusters. The calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 59 publications
4
15
0
Order By: Relevance
“…Such topologies are convenient for electron transfer from Cu or Ag to Au and easily reduce geometrical reconstruction. The geometries of Au n Cu m and Au n Ag m clusters according to PW91PW91 calculations are consistent with previous theoretical reports [3][4][5][6].…”
Section: Structures and Stabilitiessupporting
confidence: 89%
See 1 more Smart Citation
“…Such topologies are convenient for electron transfer from Cu or Ag to Au and easily reduce geometrical reconstruction. The geometries of Au n Cu m and Au n Ag m clusters according to PW91PW91 calculations are consistent with previous theoretical reports [3][4][5][6].…”
Section: Structures and Stabilitiessupporting
confidence: 89%
“…In recent years, bimetallic coinage metal clusters have attracted considerable attention both experimentally and theoretically primarily because they often exhibit distinct physical and chemical properties from the pure coinage clusters [2][3][4][5][6][7][8][9][10][11][12][13][14]. The bimetallic Au/Cu nanoparticles confined in SBA-15 have much better performance than monometallic particles in catalyzing CO oxidation even with the presence of excess H 2 [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one can see that the value of hai exhibits a sequence of anion [ neutral [ cation, which reflects that the Rh 2 Si n ? clusters are more stable than Rh 2 Si n and Rh 2 Si n -clusters [79]. In order to explore the correlation between hai and HOMO-LUMO gap, the hai values and inverse of HOMO-LUMO gaps (HL -1 ) versus n for Rh 2 Si n q clusters are shown in Fig.…”
Section: Polarizability and Inverse Of Homo-lumo Gapsmentioning
confidence: 99%
“…Recently, Guo et al studied the structures and stabilities of Au n Pd 2 and Au n Pt 2 (n=1-4) clusters [27,28], and their results indicated that the gold-doped atoms interaction is strong enough to enhance the cluster stability, and the larger the Au n cluster, smaller the distortions caused by the two Pd or Pt atoms. We have systematically reported investigations on small M 2 Au n (M=Ag, Cu; n=1-10) clusters, comparing them with their equivalent (in terms of size) pure gold clusters [29]; we found that the ground-state structures show 3D structure at n=6, 9, 10 for Ag 2 Au n and n=6, 7, 9, 10 for Cu 2 Au n clusters. This reveals that the dopant atoms dramatically affect the geometries of the ground states of the equivalent Au n clusters.…”
Section: Introductionmentioning
confidence: 92%